2015
DOI: 10.5958/2320-642x.2015.00014.9
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Phenology, Physiology and Yield Response of Different Maturity Duration Pigeon Pea Genotypes at Elevated CO2

Abstract: Three pigeon pea (Cajanus cajan L. Millsp.) genotypes-ICPL-88039, GT-1, and AKP-1-with varying crop duration, growth habit and flowering pattern were grown at ambient (390 ppm) and elevated (550 ppm) CO 2 levels in Open Top Chambers (OTCs) to assess the variability in their responses for phenology, physiology, biomass and seed yield parameters. It was observed that elevated CO 2 significantly increased the photosynthetic rate (A net), decreased the transpiration rate and increased water use efficiency (WUE). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To further complicate matters, environmental factors appear to play a substantial role in seed yield effects under e[CO 2 ], which is evidenced by the finding that smaller stimulations in yield are typically observed in FACE experiments compared to those conducted in controlled environments (Ainsworth et al, 2008 ). Furthermore, a large amount of intraspecific variability is evident in legume species with respect to the magnitude of yield gains under e[CO 2 ] (Bishop et al, 2015 ; Bunce, 2016 ; Kumagai et al, 2015 ; Li et al, 2017 ; Li et al, 2019 ; Vanaja et al, 2015 ). Intriguingly, it has been found that soybean cultivars displaying the greatest yield increases under CO 2 enrichment were not necessarily those with the highest yields under ambient [CO 2 ], but instead those that displayed the greatest yield gain under e[CO 2 ] (Li et al, 2017 ; Li et al, 2019 ).…”
Section: Effect Of Elevated [Co 2 ] On Legume Seed...mentioning
confidence: 99%
“…To further complicate matters, environmental factors appear to play a substantial role in seed yield effects under e[CO 2 ], which is evidenced by the finding that smaller stimulations in yield are typically observed in FACE experiments compared to those conducted in controlled environments (Ainsworth et al, 2008 ). Furthermore, a large amount of intraspecific variability is evident in legume species with respect to the magnitude of yield gains under e[CO 2 ] (Bishop et al, 2015 ; Bunce, 2016 ; Kumagai et al, 2015 ; Li et al, 2017 ; Li et al, 2019 ; Vanaja et al, 2015 ). Intriguingly, it has been found that soybean cultivars displaying the greatest yield increases under CO 2 enrichment were not necessarily those with the highest yields under ambient [CO 2 ], but instead those that displayed the greatest yield gain under e[CO 2 ] (Li et al, 2017 ; Li et al, 2019 ).…”
Section: Effect Of Elevated [Co 2 ] On Legume Seed...mentioning
confidence: 99%